Acute toxicity and quality of life in patients with prostate cancer treated with protons or carbon ions in a prospective randomized phase II study: The IPI trial - Habl, Gregor; Uhl, Matthias; Katayama, Sonja; Eitz, Kerstin Anne; Hatiboglu, Gencay; Hadaschik, Boris; Ellerbrock, Malte; Haberer, Thomas; Debus, Jürgen; Herfarth, Klaus (International journal of radiation oncology, biology, physics, 2016)
Purpose - The purpose of this study was to compare safety and feasibility of proton therapy with that of carbon ion therapy in hypofractionated raster-scanned irradiation of the prostate, in a prospective randomized phase 2 trial. - Methods and Materials - In this trial, 92 patients with localized prostate cancer were enrolled. Patients were randomized to receive either proton therapy (arm A) or carbon ion therapy (arm B) and treated with a total dose of 66 Gy(relative biological effectiveness [RBE]) administered in 20 fractions (single dose of 3.3 Gy[RBE]). Patients were stratified by the use of antihormone therapy. Primary endpoint was the combined assessment of safety and feasibility. Secondary endpoints were specific toxicities, prostate-specific antigen progression-free survival (PFS), overall survival (OS), and quality of life (QoL). - Results - Ninety-one patients completed therapy and have had a median follow-up of 22.3 months. Among acute genitourinary toxicities, grade 1 cystitis rates were 34.1% (39.1% in A; 28.9% in B) and 17.6% grade 2 (21.7% in A; 13.3% in B). Seven patients (8%) required urinary catheterization during treatment due to urinary retention, 5 of whom were in arm A. Regarding acute gastrointestinal toxicities, 2 patients treated with protons developed grade 3 rectal fistulas. Grade 1 radiation proctitis occurred in 12.1% (13.0% in A; 11.1% in B) and grade 2 in 5.5% (8.7% in A; 2.2% in B). No statistically significant differences in toxicity profiles between arms were found. Reduced QoL was evident mainly in fatigue, pain, and urinary symptoms during therapy and 6 weeks thereafter. All European Organization for Research and Treatment of Cancer QLQ-C30 and -PR25 scores improved during follow-up. - Conclusions - Hypofractionated irradiation using either carbon ions or protons results in comparable acute toxicities and QoL parameters. We found that hypofractionated particle irradiation is feasible and may be safe. Due to the occurrence of gel in the rectal wall and the consecutive occurrence of 2 rectal fistulas, we stopped using the insertion of spacer gel. Longer follow-up is necessary for evaluation of PFS and OS. (Ion Prostate Irradiation (IPI); NCT01641185; ClinicalTrials.gov.)